Knowledge creation enhancement in the Royal Malaysian Navy (RMN) FLeet / Shaftdean Lufty Rusland - Shaftdean Lufty , Rusland (2020)
This study aims to gauge the extent of knowledge creation processes in the Royal Malaysian Navy (RMN) fleet with the use of the SECI (socialization, externalization, combination, internalization) knowledge creation process model proposed by Nonaka and Takeuchi (1995). This is in order for the researcher to propose a knowledge creation enhancement framework to the organization. Case study method was utilized in this study and both descriptive and interpretive analyses were employed to achieve the research aims. The descriptive data were used to triangulate the interpretive data and documentation reviewed by dividing the findings in accordance to the SECI conversion process. 234 self-administered questionnaires were used to investigate to what extent the RMN fleet performs the SECI and 15 semi-structured face-to-face interviews provided insights about how the RMN fleet perform these activities. The survey data were analyzed by using Statistical Package for Social Sciences (SPSS) Version 24 software to get descriptive statistics and transcriptions from the interviews were analyzed manually by content analysis method for interpretive data, to get the themes and sub-themes of the study. NVivo 12 software were also used to managed all the data from the interviews by identifying at the noticeable patterns to be connected to the study. The findings indicate that the SECI processes were used for knowledge creation in the RMN fleet. However, some limitations minimized the benefits in all creation of knowledge modes in SECI processes within the RMN. The externalization and internalization processes in creating knowledge were seen to be slightly prominent when compared to socialization and combination, revealing that in the RMN fleet all four modes of knowledge creation have almost equal importance. However, the use of each process is mostly subjected to the higher management support and some cultural contexts. The findings also suggest that the SECI processes, regardless it is a single or as a whole process, influence the creation of knowledge by increasing the generation of ideas, documentation of knowledge, updating the knowledge and sharing of knowledge for the benefit of the organization.